2011
DOI: 10.1002/jbm.a.33236
|View full text |Cite
|
Sign up to set email alerts
|

Acid‐insoluble human dentin as carrier material for recombinant human BMP‐2

Abstract: The aim of this study is to estimate the increase of bone-inductive potency by human demineralized dentin matrix (DDM) with recombinant human bone morphogenetic protein-2 (BMP-2). Human teeth were crushed, completely demineralized in 0.6M HCl, and freeze-dried. The tooth-derived material is called DDM. The shape of DDM was a particle type and its size varied from 0.4 to 0.8 mm. The BMP-2 dose-dependent study in the rat subcutaneous tissues demonstrated that the volume of induced bone and marrow increased at a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
65
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 45 publications
(67 citation statements)
references
References 26 publications
(52 reference statements)
2
65
0
Order By: Relevance
“…2) We confirmed histologically that human completely demineralized dentin granules by hand-made method using hammer induced bone and cartilage independently at 4 weeks, 4), 5) and have obtained successful results in clinical studies of the autograft of DDM for bone regeneration.…”
Section: Introductionsupporting
confidence: 61%
“…2) We confirmed histologically that human completely demineralized dentin granules by hand-made method using hammer induced bone and cartilage independently at 4 weeks, 4), 5) and have obtained successful results in clinical studies of the autograft of DDM for bone regeneration.…”
Section: Introductionsupporting
confidence: 61%
“…A recent animal study by Kim et al demonstrated that DDM dissolves rhBMP-2 more gradually and steadily than other tricalcium phosphates (TCP) and bovine bone, establishing that particulated DDM is the most effective BMP carrier [31]. Other studies have reported that adding rhBMP-2 to DDM ensures the formation of new bone and cartilage, and DDM is absorbed and replaced by vital new bone tissue approaching almost 80% of the total volume, as indicated by histomorphometric assessment [23,45]. The current study was undertaken to evaluate, using a histomorphometric assessment, whether the addition of rhBMP-2 to DDM leads to superior bone regeneration in comparison with DDM alone or conventional DBBC.…”
Section: Discussionmentioning
confidence: 99%
“…DDM can be defined as acid-insoluble, cross-linked collagen with natural growth factors, and is composed of predominantly type I collagen (95 %) and the remaining non-collagenous proteins including small amount of growth factors 1,12) . DDM has potential to promote transformation of mesechymal stem cells into osteoblastic cells, because several well-known cytokines including BMP could be released from dentin through increased surface, enlarged dentinal tubules and loosened collagen fibers by demineralization process 3,13,14) .…”
Section: Discussionmentioning
confidence: 99%